The design method of slope stabilizing piles: A review - Mujah, Donovan; Ahmad, Fauziah; Hazarika, Hemanta; Watanabe, Naoto (Inpressco, 2013)
A comprehensive literature review was conducted to examine the current state of knowledge regarding passive piles which specifically focused on the recently adopted design methods for landslide prevention. Of all the publications compiled and reviewed for passive loading on piles, numerous efforts were found starting from over the last three decades, where major emphasis was placed on the various approaches ranging from theoretical and analytical to finite element methods. These methods have been adapted to predict the response of the piles, which also incorporates the influence of group interaction factors. Although research on passive piles subjected to lateral soil movement seems to berecent, there seemed to be a missing gap in research for pile groups used as landslide stabilizing piles. The authors believe that all of these state-of-the-art methods are widely accepted as it is supported by comparison with both field and laboratory data. Based on the review, the authors would like to highlight that further three dimensional (3D) modeling would offer another excellent alternative to study the response of those piles for landslide mitigation purposes.